1989
DOI: 10.1002/actp.1989.010400704
|View full text |Cite
|
Sign up to set email alerts
|

New m‐carborane‐containing polymeric schiff bases

Abstract: Ncw soluble m-carborane-containing polymeric SCHIFF bases are prepared by polycondensation of m-carboranylenediamine, 1,7-bis(4-aminophenylcarboxy)-m-carborane, and 1,7-bis(4-aminophenylamido)-m-carborane with different dialdehydes in solution. Optimum conditions for polymer synthesis are found. The structure of the resulting polymers is confirmed by the synthesis of model compounds not described earlier, IR spectroscopy, and elemental analysis data. Some properties of m-carborane-containing polymeric SCHIFF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For example, they serve as ligands in coordination chemistry, [39] building blocks in medicinal chemistry, [28,33,40] and as monomeric precursors for polymers. [38,41] Recently, we reported on the fluorination of the [1-H 2 Ncloso-CB 11 H 11 ] À ion (7) with elemental fluorine in anhydrous hydrogen fluoride, which results in salts of the amino-functionalized undecafluorinated anion [1-H 2 N-closo-CB 11 F 11 ] À . [14] Double deprotonation of this anion resulted in a carbon extrusion/cluster contraction reaction yielding the cyano-closo-undecaborate dianion [3-NC-closo-B 11 F 10 ] 2À , [42] which takes part in further unprecedented reactions.…”
Section: Salts Of the [1-h 2 N-closo-cb 11 H 11 ]mentioning
confidence: 99%
“…For example, they serve as ligands in coordination chemistry, [39] building blocks in medicinal chemistry, [28,33,40] and as monomeric precursors for polymers. [38,41] Recently, we reported on the fluorination of the [1-H 2 Ncloso-CB 11 H 11 ] À ion (7) with elemental fluorine in anhydrous hydrogen fluoride, which results in salts of the amino-functionalized undecafluorinated anion [1-H 2 N-closo-CB 11 F 11 ] À . [14] Double deprotonation of this anion resulted in a carbon extrusion/cluster contraction reaction yielding the cyano-closo-undecaborate dianion [3-NC-closo-B 11 F 10 ] 2À , [42] which takes part in further unprecedented reactions.…”
Section: Salts Of the [1-h 2 N-closo-cb 11 H 11 ]mentioning
confidence: 99%
“…6 They prepared several percentage of hexanol/chloroform solutions, but there has no gelation been mentioned in their work. In addition, the gel formation of polyfluorenes has been reported in single solvent-based solution; for example, good solvent (1,2,4trichlorobenzene) 7 and poor solvent (cyclohexane 8 and methylcyclohexane 9 ) are used as the solvent. Low-molecular-weight organogels were also reported, 10 resulting from noncovalent interactions, such as hydrogen bonding, π-stacking, solvophobic effects, and donor-acceptor interactions.…”
Section: Introductionmentioning
confidence: 99%
“…High boron content polyborane polymers and oligomers are of great interest for their potential ceramic precursor, boron neutron cancer therapy (BNCT), and/or optical and electronic properties . While main-chain siloxane−carborane polymers have been extensively studied, the syntheses and properties of the corresponding main-chain organo−carborane polymers , and cyclic oligomers have been less well developed. The work described herein has demonstrated that metal-catalyzed RCM and ADMET reactions of (alkenyl) 2 - o -carboranes and - m -carboranes, and potentially other dialkenylpolyboranes, can provide versatile new synthetic routes to such materials.…”
Section: Resultsmentioning
confidence: 99%